BUILDING TOURISM COMPETITIVENESS THROUGH A CUSTOMER-FOCUSED CULTURE: EVIDENCE FROM MANGGARAI BARAT, INDONESIA - Wijanarko, Adrian; Sajili, Mohamad; Poetri, Keyka (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2025)
Manggarai Barat, designated as one of the country’s ten priority destinations and home to the UNESCO World Heritage Komodo National Park, was among the regions most severely affected by the COVID-19 outbreak, experiencing sharp declines in tourist arrivals and revenue. This study explores the establishment of a customer-centric culture in local tourism enterprises in Manggarai Barat, with a focus on leadership, organizational structure, employee empowerment, communication, and strategic orientation. Using a qualitative approach, it examines case studies of Komodo Snorkel and Puri Sari Beach Hotel through in-depth interviews with senior management.The findings highlight the unique challenges of small, community-based businesses operating with limited financial resources while competing in an increasingly globalized market. Unlike larger organizations, their ability to implement customer-centric practices is shaped by leadership expertise, global exposure, and regional networks. Leaders play direct roles in service delivery, adapt strategies to evolving tourist needs, and foster collaborative cultures. Customer feedback, personalized services, and employee motivation are essential in sustaining satisfaction and generating positive word-of-mouth. Overall, the study contributes to human resource and strategic management literature by demonstrating how locally rooted firms can adopt customer-centric practices to strengthen competitiveness and resilience in Indonesia’s tourism sector.